1939
DOI: 10.3181/00379727-42-10959
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunity to Pneumococci in Rabbits Protected by Sulfapyridine.

Abstract: The results of experiments on the protection of rabbits, infected with pneumococci, by oral administration of sulfapyridine have been reported previous1y.l The purpose of this communication is to present data obtained in the study of the immunity in animals that had recovered from the infection produced under such circumstances.Rabbits weighing approximately 2 kilos were inoculated intracutaneously with 0.3 cc of a l/lOO dilution of an %hour culture of a pneumococcus type 11. The inoculum contained an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1942
1942
1956
1956

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The early development of circulating antibodies and active 'resistance was not influenced by the administration of sulfonamide (11)(12)(13).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The early development of circulating antibodies and active 'resistance was not influenced by the administration of sulfonamide (11)(12)(13).…”
Section: Discussionmentioning
confidence: 96%
“…Twenty-nine patients received initial penicillin doses of from 20,000 to 50,000 units intramuscularly; 12 patients were given 100,000 units, and three patients 300,000 units. Subsequent dosage in 33 cases ranged from 20,000 to 50,000 units every two to three hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An apparent correlation was observed not only between the survival rate and the relative antigenicity of the respective types of pneumococci, but also between the differences in the time required for the development of antibodies and the length of time during which it was necessary to continue sulfapyridine treatment. Larson, Bieter, and Levine (7,8) demonstrated that rabbits which recovered from intradermal infection with Pneumococcus Type II following treatment with sulfapyridine were highly resistant to reinfection with the homologous type of organism 30 or more days later.…”
mentioning
confidence: 99%